KAIDAH NIAT DAN PENENTUAN KESENGAJAAN PEMBUNUHAN DALAM HUKUM ISLAM - Ropei, Ahmad (Ahkam: Jurnal Hukum Islam, 2021)
This study aims to reveal the application of the rule of intent and its relevance of determination intentional murder in Islamic law. The approach used in this research is library research, with the data collected by literatural technique. The process of data analysis was carried out by descriptive-analytical techniques. The results of this study indicates that the rule of intent in Islamic law is an important instrument to determine the element of intent in a murder case. Practically, the rule to reveal the existence of a murder intent is to look into several things, including through the tools used to kill and the existence of hostility or disputes between the perpetrator and the victim before the murder occurred, where this can be used as a legal fact to explore the element of intent in the murder. Element of intent used as a prove for the perpetrator so be punished in the form of qishash.